Assessment of antibiotic prescribing pattern in pediatric patients: A cross-sectional hospital-based survey - Bhupalam Pradeepkumar; Tawfeek Alameri; Goruntla Narayana; Y Padmanabha Reddy; Jinka Dasaratha Ramaiah (Wolters Kluwer Medknow Publications, 2017)
Background: Irrational usage of antibiotics increases the risk for the antimicrobial resistance, leads to increase morbidity, mortality, and economic burden for health care. India is a lower-middle income developing country in south Asia that has high potential for overuse and misuse of antibiotics and has less public awareness of antimicrobial resistance. The World Health Organization (WHO) developed the prescribing indicators to measure the rational usage of drugs in primary care and to assess the prescribing pattern of antibiotics. Aim: The aim of the study was to assess the prescribing pattern of antibiotics in pediatric patients of Anantapur district, Andhra Pradesh, India. Subjects and Methods: A cross-sectional and prospective study was carried out in private pediatric specialty hospitals in urban areas of Anantapur district. Sample size was calculated using single population proportion formula. A total number of 845 pediatric in-patients were included for the study. Patients' demographic characters, diagnosis, and drugs prescribed were recorded in a prestructured and validated data collection form. Results: An average of 3.53 drugs prescribed per patient encounter, which was higher than WHO prescribed indicator standard value 2. The present study reveals that the percentage of encounters with antibiotics was 50.05% (423), which was higher than WHO standard (20.0-26.8%). Among 423 antibiotic prescriptions, 23.43% (198) prescribed with generic names and 91.48% antibiotics were prescribed from essential drug formulary list. Conclusion: Prescription patterns and usage of antibiotics in this study was inappropriate in comparing our results with WHO prescribing indicators. Effective interventions are required to reduce inappropriate antibiotic prescriptions.